2016
DOI: 10.1007/s12185-016-1945-y
|View full text |Cite
|
Sign up to set email alerts
|

Iron chelation therapy of transfusion-dependent β-thalassemia during pregnancy in the era of novel drugs: is deferasirox toxic?

Abstract: The life expectancy of thalassemic patients has increased, and now approaches that of healthy individuals, thanks to improved treatment regimens. However, pregnancy in women with β-Thalassemia Μajor remains a challenging condition. Recent advances in managing this haemoglobinopathy offer the potential for safe pregnancies with favorable outcome. However, clinical data regarding the use of chelation therapy during pregnancy are limited, and it is unclear whether these agents impose any risk to the developing fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Successful pregnancies following unintentional treatment with deferiprone or deferasirox have been reported 8,39,40,41. Nonetheless, the use of oral iron chelators is contraindicated in pregnant women, because of the lack of controlled data.…”
Section: Pregnancy Management In Thalassemia Majormentioning
confidence: 99%
“…Successful pregnancies following unintentional treatment with deferiprone or deferasirox have been reported 8,39,40,41. Nonetheless, the use of oral iron chelators is contraindicated in pregnant women, because of the lack of controlled data.…”
Section: Pregnancy Management In Thalassemia Majormentioning
confidence: 99%
“…DFX has also been assigned to pregnancy category C by the FDA, as animal studies have revealed evidence of embryo fetotoxicity. These studies showed decreased offspring viability and increased renal anomalies (Anastasi et al, 2011;Vini et al, 2011;Diamantidis et al, 2016).…”
Section: Pregnancy and Chelationmentioning
confidence: 99%
“…20 According to experts, DFO should be avoided during the first trimester, but subcutaneous administration may be considered in the second and third trimesters for patients with a strong indication for treatment. 114 As to oral chelators, according to experimental models placental transfer of DFX is minimal in rats, 115 but fetal outcome data in humans are limited to spontaneous pregnancy case reports, 116 , 117 and based on the product label DFX use is contraindicated in pregnant women.…”
Section: Antepartum Managementmentioning
confidence: 99%